Die Beziehungen der Herrnhuter Brüdergemeine zu Ungarn und Siebenbürgen - Hausmann, Gerhard (Unitas Fratrum, 2022)
A particular area of the Moravians’ activity was their diaspora work, which aimed to seek out the ‘pious in the land’ in a largely rationalistic church and society, to provide them with pastoral care, and to bring them into contact with each other. As early as the 1730s, Moravians were active in South-East Europe. In addition to the reports of these ‘diaspora workers’, there were also correspondents who informed the Preachers’ Conference in Herrnhut about church life in their respective territories. The example of the pastor of Oberschützen, Gottlieb August Wimmer, who reported from Hungary from 1835 to 1848, is used to illustrate this aspect of the connection between Herrnhut and South-East Europe – a connection that largely came to an end during the second half of the nineteenth century.